Effect of Antimalarial Drugs on the Immune Response to Intramuscular Rabies Vaccination Using a Postexposure Prophylaxis Regimen. (2nd November 2019) - Endy, Timothy P; Keiser, Paul B; Cibula, Don; Abbott, Mark; Ware, Lisa; Thomas, Stephen J; Polhemus, Mark E
Abstract: Background: Chloroquine can impair the immune responses to intradermal rabies vaccination. Current guidelines recommend an extra intramuscular dose be given for postexposure prophylaxis in previously unvaccinated persons taking any antimalarial drug. Methods: We conducted a randomized, open-label, single-site study in 103 previously unvaccinated healthy adults age ≥18 to ≤60 years old to evaluate the effects of chloroquine, atovaquone/proguanil (Malarone), and doxycycline on the antibody response to a purified chick embryo cell vaccine, given on a postexposure prophylaxis schedule. All treatment groups received antimalarials 14 days prior to and during vaccination. Results: All subjects achieved accepted neutralizing antibody titers of ≥0.5 IU/mL following the second rabies vaccination dose and maintained this protection through the duration of the study. We observed a reduction in rabies antibody geometric mean titer in the chloroquine versus control groups 28 days after vaccination: 2.3 versus 6.87 IU/mL, respectively ( P < .001, t test). A significant difference was not observed for those taking Malarone or doxycycline. Conclusions: We conclude that there is no reduction of rabies antibody response in subjects taking Malarone or doxycycline, but a significant reduction in those taking chloroquine; however, accepted antibody levels were achieved for all 3 antimalarials. Clinical Trials Registration: NCT02564471. Abstract : This randomized, controlled trial in 103 adults who received rabies vaccine and antimalarials found no reduction of rabies antibody response in subjects taking Malarone or doxycycline but reduction from chloroquine; however, accepted antibody levels were achieved for all 3 antimalarials.